Susceptibility Pattern of Caspofungin-Coated Gold Nanoparticles Against Clinically Important Candida Species - Zahra Salehi; Azam Fattahi; Ensieh Lotfali; Abdolhassan Kazemi; Ali Shakeri-Zadeh; Saman Ahmad Nasrollahi (Tabriz University of Medical Sciences, 2021)
Purpose: The present study was performed to examine whether caspofungin-coated gold nanoparticles (CAS-AuNPs) may offer the right platform for sensitivity induction in resistant isolates. Methods: A total of 58 archived Candida species were enrolled in the research. The identification of Candida spp. was performed using polymerase chain reaction-restriction fragment length polymorphism and HWP1 gene amplification approaches. The conjugated CAS-AuNPs were synthesized and then characterized using transmission electron microscopy (TEM) and Zetasizer system to determine their morphology, size, and charge. Furthermore, the efficacy was assessed based on the Clinical and Laboratory Standards Institute M60. Finally, the interaction of CAS-AuNPs with Candida element was evaluated via scanning electron microscopy (SEM). Results: According to the TEM results, the synthesized CAS-AuNPs had a spherical shape with an average size of 20 nm. The Zeta potential of CAS-AuNPs was -38.2 mV. Statistical analyses showed that CAS-AuNPs could significantly reduce the minimum inhibitory concentration against C. albicans (P=0.0005) and non-albicans Candida (NAC) species (P<0.0001). All isolates had a MIC value of ≥ 4 µg/ml for CAS, except for C. glabrata. The results of SEM analysis confirmed the effects of AuNPs on the cell wall structure of C. globrata with the formation of pores. Conclusion: According to findings, CAS-AuNPs conjugates had significant antifungal effects against Candida spp. Therefore, it can be concluded that the encapsulation of antifungal drugs in combination with NPs not only diminishes side effects but also enhances the effectiveness of the medications.